Konseling Kognitif Behavioral Dengan Teknik Self Management dan Teknik Modeling Terhadap Motivasi Berprestasi Ditinjau dari Tipe Belajar - Ni Wayan Karyani; I Ketut Dharsana (Bisma The Journal of Counseling, 2018)
The purpose of this research for to known the effectiveness of cognitive behavioral counseling with Self Management Technique and Modeling Technique toward Need for Achievment Reviewed on Studying Type. This research design by two factor design. The sampling are 90 person students of X grade SMA Negeri 1 Kintamani academic year 2015/2016 and analyzed by analysis of varians (anava) and Tukey. The result of the research is: (1) there are a difference of need for achievement between students who follows humanistic counseling with self management technique with students who follows modeling.technique.; (2) there are a difference of need for achievement reviewed of studying type. (3) there are an interactions effect of humanistic counseling with self management technique and modeling technique with studying type of need for achievement.; (4) there are a difference of need for achievement between students who follows humanistic counseling with self management with students who follows modeling technique on students based auditory studying type; (5) there are no difference of need for achievement between students who follows humanistic counseling with self management technique with modeling technique on students based visual studying type; (6) there are no difference of need for achievement between students who follows self management technique with modeling technique on students based kinesthetic.